2006
DOI: 10.1002/app.25173
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of polypropylene composites based on natural fibers subjected to multiple extrusion cycles

Abstract: The influence of multiple extrusion cycles on the behavior of natural fibers-reinforced polypropylene was studied. Composites were fabricated with 20 wt % of flax fibers. Final fibers dimensions (length and diameter) were measured by means of optical microscopy. Mechanical properties of matrix and composites were measured after each extrusion cycle. It was observed that the elastic modulus increased by fibers incorporation. The elastic modulus of the matrix was higher after the first process cycle than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 18 publications
(21 reference statements)
5
35
0
Order By: Relevance
“…In this study, tensile properties of composites remained quite stable until the third injection step however in further recycling steps significant drop in tensile properties were observed because of the matrix degradation and shortening of fibers. Moran et al (2007) reported that shortening of fiber lengths as a result of reprocessing steps had a certain effect on the mechanical properties of the composite materials. Migneault et al (2008) explored that there was a linear relationship between fiber length and mechanical properties of the composites.…”
Section: Introductionmentioning
confidence: 98%
“…In this study, tensile properties of composites remained quite stable until the third injection step however in further recycling steps significant drop in tensile properties were observed because of the matrix degradation and shortening of fibers. Moran et al (2007) reported that shortening of fiber lengths as a result of reprocessing steps had a certain effect on the mechanical properties of the composite materials. Migneault et al (2008) explored that there was a linear relationship between fiber length and mechanical properties of the composites.…”
Section: Introductionmentioning
confidence: 98%
“…16,[19][20][21][22][23] The archival publications indicate that water absorption and thickness swelling behavior of reprocessed natural fiber plastic composites depend on a numerous factors including interface quality, chemical composition, fiber length and distribution, and density. The results confirmed that generally the recycling process boosted water resistance and dimensional stability in the studied formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Among other desirable properties, the composites should possess enhanced biodegradability and should be reusable. [2][3][4] The removal of heavy metals from wastewaters is an important industrial challenge and is a concern to human health. Several solid adsorbents have been proposed for the removal of heavy metals from aqueous streams, for example, ion-exchange resins, 5 membrane filters, 6 metal hydroxide, 7 activated carbons, 8 and porous polymer beads.…”
Section: Introductionmentioning
confidence: 99%